THE TYPOLOGY OF TRADITIONAL HOUSE: BALE TANI IN SADE VILLAGE, LOMBOK, WEST NUSA TENGGARA - Khalid Abdul Mannan; Tri Harso Karyono; Djoko Santoso (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
The lack of knowledge of the present generation in understanding the cultural heritage of the ancestors as well as the socio-cultural changes is due to the advancement of tourism. This becomes a phenomenon that could result in the loss of local architectural knowledge, and the loss of cultural values as it is especially the case in the traditional house of Sade village. In an effort to explore the condition, this study on typology of traditional house, especially traditional house of Bale Tani in Sade village, Lombok, West Nusa Tenggara was conducted. In addition to socio-cultural factors, there are other factors that also affect the variety types of its forms such as climate, technology, land selection, availability of materials and construction method.The research used qualitative method with naturalistic approach supported by literature and comparative study. The result of the research indicates that there has been a transformation process in the form of traditional house of Bale Tani but it is not dominant (it does not affect the visual form as a whole), it has slow progress (it happens within the long time span) and it happens on some parts/elements of Bale Tani only. Factors that influence the change are endogenous (understanding the cultural values by the Sade society) and exogenous factors that is the influence of social culture (tourism).Keywords: Typology, traditional house, Bale Tani